Identifikasi Penentuan Lokasi Prioritas Ruang Terbuka Hijau (RTH) di Kota Solok - Delisa Septya; Endah Purwaningsih (Lembaga Yasin AlSys, 2026)
The rapid growth of built-up areas has the potential to drive land-use conversion and reduce green open space, even though such areas are essential for controlling increases in air temperature and maintaining urban comfort. This study aimed to identify areas with potential to be developed as priority green open space zones in Solok City. This descriptive quantitative research used a sample of green open space areas in Solok City selected through random sampling. Data were collected through literature review and secondary data from relevant agencies, and were analyzed using three main parameters, namely comfort index, vegetation index, and population density. These parameters were processed using a weighted overlay method in ArcGIS 10.8. The results showed that vegetation density had NDVI index values ranging from -0.448622 to 0.931691, thermal comfort levels ranged from 14.8472–33.524 °C, and population density fell into categories from sparse to very dense. Based on these three parameters, two classes of priority green open space locations with the highest scores were obtained. The first priority locations covered an area of 4.62 km² (7.86%) of Solok City, encompassing 12 urban villages, with Laing Urban Village as the only urban village not included in the first-priority class. The second priority locations covered an area of 7.61 km² (12.95%) of Solok City and encompassed all urban villages, with the largest area located in Nan Balimo Urban Village (1.12 km²). These findings provide a spatial basis for more targeted determination of locations for green open space development and contribute to efforts to enhance thermal comfort and urban environmental quality in Solok City.